An exploration into some dominant features of Filipino social behavior - Flores Bonifacio, Manuel (Philippine Journal of Psychology, 1977)
Explores dominant features of Filipino social behavior using a symbolic interactionist perspective. Specifically, the paper attempts to analyze the Filipino's personalism, intrusion, privacy, and submissiveness and the concepts of success and failure. The analysis is predicated on the idea that behavior is to a large extent determined by the sociocultural environment.